NEGOSIASI MUSIKAL ORKES KERONCONG FARIES NAFISA NUSANTORO DALAM PERTAUTAN PERKEMBANGAN MUSIK POPULER DANGDUT - Raihan Jelang Ramadhan; Kiswanto (Universitas Hamzanwadi, 2025)
This paper aims to uncover and explain the process of adaptation and negotiation of keroncong music amidst the dominance of popular dangdut music culture. This study focuses on the cultural dialectics undertaken by Faries Nafisa Nusantoro and Sanggar Rindu Malam in their efforts to confront the dominance of mainstream music. This research is based on an ethnographic approach conducted through building direct involvement in the midst of the study, supported by techniques such as observation, interviews, documentation, and literature review. This study produces findings in the form of adaptations referring to the marriage (hybridization) between keroncong music and dangdut music, musical negotiations that occur in the development of keroncong music, and its significance in the development of keroncong music in meeting the needs of the music industry in Indonesia. The findings of this research are expected to provide discourse and knowledge that contribute to the preservation and development of keroncong music in Indonesia.